Pengaruh Massage Effleurage dan Aromatheraphy Peppermint terhadap Intensitas Nyeri Pasien Post Sectio Caesarea dengan Riwayat Eklampsia - Dian Eka Putri; Sri Andar Puji Astuti; Sukmawati Sukmawati; Rindika Seftia Handini (Universitas Batanghari Jambi, 2023)
Preeclampsia is one of the contributors to maternal and child mortality in the world, WHO noted that preeclampsia occurs with an incidence of 3-10% of total pregnancies. The condition of preeclampsia can develop into eclampsia which is characterized by seizures and decreased consciousness so that CS surgery is carried out to save the mother and baby. Sectio caesarea delivery has higher pain which is around 27.3% compared to normal delivery which is around 9%. Peppermint aromatherapy and effleurage massage are non-pharmacological alternatives to reduce pain that provide a distraction and relaxation effect. This reserarch to analyze and prove the theory of interventional massage effleurage with peppermint aromatherapy can reduce the intensity of postoperative pain SC (eclampsia). The design of this study was a quasi-experimental design with a pretest-posttest non-equivalent control group design. Data collection techniques through interviews, observation, physical examination and documentation. The research was conducted in the postpartum room at Sungai Dareh Hospital, Dharmasraya Regency with a total sample of 30 people taken by convenience sampling. Pain intensity was measured before and after giving effleurage massage with peppermint aromatherapy once a day for 3 days of administration. This research instrument uses the Numerical Rating Scale (NRS). The result is effleurage massage with peppermint aromatherapy for 3 days showed a statistically significant difference (p=0.000). Before giving the action the average pain intensity was on a scale of 8.33 (severe pain category) and after being given the action the pain intensity experienced a decrease in the average scale of 2,03 (mild pain category). There is an effect of effleurage massage with peppermint aromatherapy on reducing pain intensity in postoperative SC (eclampsia) patients. Nurses and midwives can practice giving such therapy as non-pharmacological therapy for pain management.Â